Laser-Induced Fluorescence Spectroscopy in the Diagnosis of Tissue Hypoxia (Review) - Anastasiya S. Babkina (Obŝaâ Reanimatologiâ, 2019)
The aim of review is to discuss the results of studies on diagnosis of tissue hypoxia by laser-induced spectroscopy, as well as to identify promising trends and prospects of this technique for its further application in experimental and clinical medicine.The review presents the findings of studies of the fluorescence intensity of endogenous fluorophore molecules (reduced nicotinamide adenine dinucleotide, oxidized flavin adenine dinucleotide) as markers of ischemic injury of internal organs (brain, heart, liver, kidneys, etc.). The principles of fluorescence laser-induced spectroscopy in vivo are discussed. The historical aspects of the subject are also covered. The results of the use of the technique in experimental and clinical studies of tissue hypoxia and ischemia are shown. Difficulties in interpreting the intensity values of autofluorescent signal of the studied molecules are revealed. It was noted that the tissue autofluorescence in a long-term anoxia remains unknown, and there are no structured ideas about the impact of exogenous and endogenous factors on autofluorescence intensity.In conclusion, the use of laser-induced fluorescence spectroscopy to diagnose tissue ischemia is a promising area of experimental and clinical medicine, which still has various unresolved issues, despite a large number of studies in this domain.